2014
DOI: 10.3109/03009734.2014.922649
|View full text |Cite
|
Sign up to set email alerts
|

The choice of anaesthetic—sevoflurane or propofol—and outcome from cancer surgery: A retrospective analysis

Abstract: Background Commonly used inhalational hypnotics, such as sevoflurane, are pro-inflammatory, whereas the intravenously administered hypnotic agent propofol is anti-inflammatory and anti-oxidative. A few clinical studies have indicated similar effects in patients. We examined the possible association between patient survival after radical cancer surgery and the use of sevoflurane or propofol anaesthesia.Patients and methods Demographic, anaesthetic, and surgical data from 2,838 patients registered for surgery fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
160
5
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(177 citation statements)
references
References 38 publications
10
160
5
2
Order By: Relevance
“…45 Furthermore, a retrospective study, reporting the data from 2838 patients registered for surgery for breast, colon, or rectal cancer, showed that propofol anesthesia might be better than sevoflurane in surgery for some cancer types for 1-year survival, however, after adjustment for several confounders, the observed differences were not statistically significant. 46 These studies are summarized in Table 2.…”
Section: Influence Of Anesthetic Type On Cancer Outcomes and Recurrencementioning
confidence: 99%
“…45 Furthermore, a retrospective study, reporting the data from 2838 patients registered for surgery for breast, colon, or rectal cancer, showed that propofol anesthesia might be better than sevoflurane in surgery for some cancer types for 1-year survival, however, after adjustment for several confounders, the observed differences were not statistically significant. 46 These studies are summarized in Table 2.…”
Section: Influence Of Anesthetic Type On Cancer Outcomes and Recurrencementioning
confidence: 99%
“…Enlund et al [4] reported in a previous clinical study that patients anesthetized with sevoflurane may have shorter overall survival rates than patients anesthetized with propofol during cancer surgery. Several recent in vitro studies Two percent sevoflurane at 100 or 300 mg/dl of glucose concentration with various insulin concentrations.…”
mentioning
confidence: 98%
“…In a retrospective study, sevoflurane, one of the most commonly used volatile general anesthetics for cancer surgery patients, leads to lower overall survival rates than propofol [4]. Furthermore, several in vitro studies have revealed that sevoflurane increases cancer cell proliferation [5,6].…”
mentioning
confidence: 99%
“…A retrospective analysis of breast, colon and rectal cancer surgery found an improved one-and five-year overall survival of 4.7% and 5.6%, respectively, with total intravenous anaesthesia compared with sevoflurane anaesthesia [26], and preliminary data from an ongoing prospective randomised controlled trial for radical cystectomy supports these findings by demonstrating improved immune function with total intravenous anaesthesia, namely enhanced cell-mediated immunity [27].…”
Section: A Peri-operative 'Perfect Storm'mentioning
confidence: 92%